Legal consciousness as an element legal culture of the Kazakhstan society. (Journal of actual problems of jurisprudence, 2016)
This article is devoted to analysis of justice as an important element of the legal culture of the modern Kazakh society. The aim of the article is to study the sense of justice, which has an active effect on theregulation of many vital processes occurring in the state and society. The article describes the essence of the concept of justice, basic approaches to understanding justice. Furthermore the author pays particular attention to the legal ideology and legal psychology, which, when the cause formation of a single phenomenon– legal consciousness. Article is based on a review of scientific studies of domestic and foreign authors on the study of justice and its implications for the formation of the legal culture of society.
Keywords: legal consciousness; legal culture; legal ideology; legal psychology; culture; democratic state; civil society; state; society